Sosialisasi Mencegah Hoax Menjelang Pilkada 2024 Kepada Pemilih Pemula di Madrasah Aliyah Zainatul Ulum Aceh Barat - Amri Wahid Hidayat; Sopar Sopar; Ligar Abdillah; Riki Yulianda; Saiful Asra; Afriani Maifizar (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
First-time voters play a crucial role in the electoral and regional election (Pilkada) processes and represent one of the most vulnerable groups to the influence of misinformation, which often proliferates during election periods. Their high exposure to social media significantly increases the likelihood of encountering and spreading hoaxes. Therefore, it is essential to enhance their understanding and awareness to prevent them from becoming both targets and agents of misinformation. As part of a community engagement initiative ahead of the 2024 regional elections, lecturers from Teuku Umar University conducted a political education program aimed at senior high school students—who largely comprise first-time voters. This outreach focused on raising awareness about the dangers of hoaxes and how to avoid their spread. The primary objective of this initiative was to increase first-time voters' awareness of the importance of verifying information before accepting or disseminating it. In addition, it sought to provide knowledge on how to identify hoaxes and recognize credible information sources. The method employed was participatory socialization, involving presentations on hoaxes, video screenings illustrating their dangers and impacts, and interactive Q&A sessions between facilitators and student participants. This activity successfully enhanced participants’ understanding and encouraged them to actively seek accurate information, thereby reducing the risk of being misled by false narratives